Protection of the Prodomain α1-Helix Correlates with Latency in the Transforming Growth Factor-β Family. Issue 5 (15th March 2022) - Le, Viet Q.; Iacob, Roxana E.; Zhao, Bo; Su, Yang; Tian, Yuan; Toohey, Cameron; Engen, John R.; Springer, Timothy A.
Graphical abstract: Highlights: How latency is achieved in only a TGF-β family subset is incompletely understood. Family members adopt 3 overall conformations with no clear correlation to latency. Latency strongly correlated with protection of the prodomain α1-helix from HDX. α1-helix protection coincided with greater buried surface area and number of bonds. Among diverse TGF-β structures, we identified a distinguishing feature of latency. Abstract: The 33 members of the transforming growth factor beta (TGF-β) family are fundamentally important for organismal development and homeostasis. Family members are synthesized and secreted as pro-complexes of non-covalently associated prodomains and growth factors (GF). Pro-complexes from a subset of family members are latent and require activation steps to release the GF for signaling. Why some members are latent while others are non-latent is incompletely understood, particularly because of large family diversity. Here, we have examined representative family members in negative stain electron microscopy (nsEM) and hydrogen deuterium exchange (HDX) to identify features that differentiate latent from non-latent members. nsEM showed three overall pro-complex conformations that differed in prodomain arm domain orientation relative to the bound growth factor. Two cross-armed members, TGF-β1 and TGF-β2, were each latent. However, among V-armed members, GDF8 was latent whereas ActA was not. All open-armed members, BMP7, BMP9, and BMP10, were non-latent. Family members exhibited remarkably varying HDX patterns, consistent with large prodomain sequence divergence. A strong correlation emerged between latency and protection of the prodomain α1-helix from exchange. Furthermore, latency and protection from exchange correlated structurally with increased α1-helix buried surface area, hydrogen bonds, and cation-pi bonds. Moreover, a specific pattern of conserved basic and hydrophobic residues in the α1-helix and aromatic residues in the interacting fastener were found only in latent members. Thus, this first comparative survey of TGF-β family members reveals not only diversity in conformation and dynamics but also unique features that distinguish latent members.